Factors Influencing Muzzaki's Interest In Paying Zakat Via Digital Payments - Yuyun Madia; Dedy Rachmad (Iqtishaduna: Jurnal Ilmiah Ekonomi Kita)
This research investigates the influence of attitudes, subjective norms, and perceptions on muzzaki's interest in paying zakat via digital payments. This research uses quantitative methods. The research population is Bogor city residents of productive age. The sampling technique used was simple random sampling, with a sample of 126 respondents. The data sources used are primary and secondary data. Primary data was obtained by distributing questionnaires directly to respondents in Bogor, while secondary data was obtained through literature reviews from various sources such as journals, books, and official websites. The research findings show that attitudes and subjective norms positively affect interest in paying zakat via digital payments. Perception does not affect interest in paying zakat via digital payments. Theoretically, this research contributes to understanding digital zakat payment behavior in Indonesia. In practical terms, this underlines the need for zakat management bodies to increase interest and accessibility in digital payments, ensuring efficient collection and distribution of zakat. The implications of this research extend to digital financial platforms and policymakers, emphasizing the importance of user-friendly and trustworthy digital zakat services.